1999
DOI: 10.1136/aim.17.1.5
|View full text |Cite
|
Sign up to set email alerts
|

Western, Minimal Acupuncture for Neck Pain: A Cohort Study

Abstract: Summary

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 7 publications
0
5
0
1
Order By: Relevance
“…Two studies in general practice showed that 67%-76% of patients with neck pain were much better or cured following acupuncture, 19;20 and acupuncture in general practice can be cost effective. 21 Whereas most patients presenting with neck pain in primary care will have pain of short duration (24 hours to three months in Ross's study), 20 patients attending a secondary care clinic usually suffer chronic pain and the pain clinic is often the last resort for patients who have tried and failed to respond to the usual treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies in general practice showed that 67%-76% of patients with neck pain were much better or cured following acupuncture, 19;20 and acupuncture in general practice can be cost effective. 21 Whereas most patients presenting with neck pain in primary care will have pain of short duration (24 hours to three months in Ross's study), 20 patients attending a secondary care clinic usually suffer chronic pain and the pain clinic is often the last resort for patients who have tried and failed to respond to the usual treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Daneben haben wir mehrere klinische Studien publiziert, deren Ergebnisse in Tabelle 1 zusammengefasst sind [7,8,9,10,11,12]. Schließlich haben wir die Wirksamkeit der Akupunktur anhand zahlreicher systematischer Reviews und Meta-Analysen evaluiert (Tabelle 2) [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27].…”
Section: Akupunktur Wirksamkeitunclassified
“…In a cohort study, minimal acupuncture was given to 32 patients with acute neck pain. 15 Neck pain scores, measured by the Northwick Park Neck Pain questionnaire, fell from an average of 12.1 (±5.4) before treatment to 4.8 (±5.6) at three months (p<0.001). Three months after acupuncture treatment, 76% of patients reported themselves 'much better'.…”
Section: Clinical Trialsmentioning
confidence: 99%
“…It is noteworthy that the trial with the weakest design (uncontrolled cohort study) was the only one that generated a positive result. 15 I would argue, however, that results of clinical trials can be valuable, regardless of direction of outcome.…”
Section: Clinical Trialsmentioning
confidence: 99%